ITRAQ-based proteomics analysis of autophagy-mediated immune responses against the vascular fungal pathogen Verticillium dahliae in Arabidopsis. Issue 4 (3rd April 2018) - Wang, Fu-Xin; Luo, Yuan-Ming; Ye, Zi-Qin; Cao, Xue; Liang, Jing-Nan; Wang, Qian; Wu, Yao; Wu, Jia-He; Wang, Hai-Yun; Zhang, Min; Cheng, Huan-Qing; Xia, Gui-Xian
ABSTRACT: The mechanisms underlying the functional link between autophagy and plant innate immunity remain largely unknown. In this study, we investigated the autophagy-mediated plant defense responses against Verticillium dahliae ( V. dahliae ) infection by comparative proteomics and cellular analyses. An assessment of the autophagy activity and disease development showed that autophagic processes were tightly related to the tolerance of Arabidopsis plant to Verticillium wilt. An isobaric tags for relative and absolute quantification (iTRAQ)-based proteomics analysis was performed, and we identified a total of 780 differentially accumulated proteins (DAPs) between wild-type and mutant atg10-1 Arabidopsis plants upon V. dahliae infection, of which, 193 ATG8-family-interacting proteins were identified in silico and their associations with autophagy were verified for several selected proteins. Three important aspects of autophagy-mediated defense against V. dahliae infection were revealed: 1) autophagy is required for the activation of upstream defense responses; 2) autophagy-mediated mitochondrial degradation (mitophagy) occurs and is an important player in the defense process; and 3) autophagy promotes the transdifferentiation of perivascular cells and the formation of xylem hyperplasia, which are crucial for protection against this vascular disease. Together, our results provide several novel insights for understanding the functional association between autophagy and plant immune responses.